2023
DOI: 10.2174/1568026623666230222094517
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Biomarkers for COVID-19 Morbidity and Mortality

Abstract: Background and Objective: This retrospective study aims to disclose further early parameters of COVID-19 morbidity and mortality. Methods: Three hundred and eighty-two COVID-19 patients, recruited between March and April 2020, were divided into three groups according to their outcome: (1) hospital ward group (patients who entered the hospital wards and survived); (2) intensive care unit (ICU) group (patients who attended the ICU and survived); (3) the deceased group (patients admitted to ICU with a fatal out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Nowadays, both people and scientific community alerts are lower, mainly because the mortality level has drastically reduced; nonetheless, every day, people still die from COVID-19 [ 15 ]. Alterations in the complete blood count are known to be present in patients with COVID-19 [ 48 , 49 ], but only relatively few studies investigated the possibility of identifying these alterations as prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, both people and scientific community alerts are lower, mainly because the mortality level has drastically reduced; nonetheless, every day, people still die from COVID-19 [ 15 ]. Alterations in the complete blood count are known to be present in patients with COVID-19 [ 48 , 49 ], but only relatively few studies investigated the possibility of identifying these alterations as prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, both people and community alerts are lower, mainly because the mortality has drastically reduced; nonetheless, every day, people still die from COVID-19 [15]. Alterations in the complete blood count are known to be present in patients with COVID-19 [48,49], but relatively only a few studies investigated the possibility of identifying these alterations as prognostic factors…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, a D-dimer level equal to or greater than 2.0 µg/mL has been linked to increased mortality, meaning that monitoring D-dimer levels is of prognostic value and essential for appropriate patient management, with further value in identifying patients who may benefit from anticoagulation therapy. [28][29][30][31][32]…”
Section: Fibrin Degradation Products (Fdps)mentioning
confidence: 99%
“…Studies of COVID-19 patients have often reported increased CRP levels, with slight elevations in the initial stages of the disease. 32 During this stage of the illness, CRP levels rise due to the increased activity of angiotensin II on the AT1 receptor, which occurs as a result of the interaction between SARS-CoV-2 and ACE-2. 34 It has been suggested that CRP could be used to monitor disease course as the levels correlate with disease severity.…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation